Perlindungan Hukum Hak Cipta Terhadap Pemutaran Lagu dalam Live Music Performance Perspektif Undang-Undang Hak Cipta dan Hifz Al-Mal di Kafe Purwokerto - Subekti, Ahmad; Niswah, Eva Mir'atun (El-Uqud: Jurnal Kajian Hukum Ekonomi Syariah, 2024)
Purwokerto has several cafes that use live music to attract customers. In live music, the performers present other people's songs in public with commercial purposes or to seek profit from the song. On the other hand, there are regulations governing the use of other people's creative works. The purpose of this study is to determine the procedure for playing songs at live music performances in cafes in Purwokerto and how the legal protection for playing songs in live music in cafes in Purwokerto is from the perspective of Copyrights Act and hifz al-mal. This study uses an empirical legal approach to analyze the cafe's compliance with economic rights in copyright. The type of research is field research. The results of the study indicate that copyright infringement is more relevant and serious in the context of large concerts that have a significant financial impact, where the use of songs without permission can substantially harm the copyright owner. In contrast, live music performed in cafes with minimal income and driven by humanitarian intentions to entertain or support the community is not considered a significant copyright infringement from a humanitarian perspective and the principle of hifz al-mal. This is due to its small financial impact and underlying good intentions, however, efforts are still needed to respect copyright in the long term in accordance with the principles of justice and protection of property in Copyrights act and hifz al-mal.